Microwave assisted effective synthesis of CdS nanoparticles to determine the copper ions in artichoke leaves extract samples by flame atomic absorption spectrometry - Saylan, Meltem; Metin, Berfin; Akbiyik, Hilal; Turak, Fatma; Cetin, Gulten; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
In this study, an accurate and sensitive analytical strategy based on cadmium sulfide nanoparticles assisted dispersive solid phase extraction (CdS-NPs-DSPE) was developed for the preconcentration/separation of copper ions in the extract of artichoke leaves. The CdS-NPs-DSPE method was combined with slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS) for the first time. The CdS-NPs were synthesized using microwave -assisted reaction as a new and rapid synthesis method for the CdS precursor solution. The morphology and structure of the synthesized sorbent were characterized using SEM, XRD, and FT-IR. The optimum conditions of the method were as follows: 40 mL sample volume, 0.10 mL of pH 4.0 buffer solution, 7.5 mg CdS NPs, 30 s sonication period, and 100 mu L of concentrated HNO3. According to the experimental results, the calibration plot was linear in the concentration range of 2.5-30 mu g/L, with a detection limit of 0.71 mu g/L. The enhancement in detection power was calculated as 162-folds based on LOD comparison. The reliability and applicability of the proposed method were validated by spiking artichoke leave extracts at different concentrations. The percent recoveries calculated for 50 and 150 mu g/L piked samples were 87 +/- 12.6 % and 116.8 +/- 3.2 %, respectively. These findings verify that the proposed method can be used for accurate and precise determination of copper ions in artichoke leaves.
Keywords: Copper; Cadmium sulfide nanoparticles; Artichoke leaves; Dispersive solid phase extraction; Flame atomic absorption spectrometry; SOLID-PHASE EXTRACTION; HEAVY-METAL IONS; TRACE DETERMINATION; WATER SAMPLES; PRECONCENTRATION; FOOD; ADSORBENT; NI; CU; NANOFLOWERS; Chemistry; Food Science & Technology